2011
DOI: 10.1007/s10877-011-9308-y
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative EEG Method for Detecting Post Clamp Changes During Carotid Endarterectomy

Abstract: By applying automatic data-driven feature extraction and classification to short EEG records, it is possible to construct subject-independent computational models that can detect subtle post clamp changes possibly caused by small perturbations in cerebral blood flow. These subtle changes are missed by visual inspection of the EEG and by other quantitative EEG techniques such as r-sBSI and r-tBSI. Within our subject group, the intricate post-clamp EEG signatures were predominantly anterior, bilateral, and had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…EEG and quantitative EEG techniques have been used to identify ischemia during neurosurgical and interventional neuroradiology vascular procedures (Plestis, Loubser et al 1997, Laman, van der Reijden et al 2001, Pinkerton 2002, van Putten, Peters et al 2004, Botes, Le Roux et al 2007, Ballotta, Saladini et al 2010, Mishra, Banday et al 2011, Skordilis, Rich et al 2011). …”
Section: Indications For Cceegmentioning
confidence: 99%
“…EEG and quantitative EEG techniques have been used to identify ischemia during neurosurgical and interventional neuroradiology vascular procedures (Plestis, Loubser et al 1997, Laman, van der Reijden et al 2001, Pinkerton 2002, van Putten, Peters et al 2004, Botes, Le Roux et al 2007, Ballotta, Saladini et al 2010, Mishra, Banday et al 2011, Skordilis, Rich et al 2011). …”
Section: Indications For Cceegmentioning
confidence: 99%
“…EEG is very sensitive in detecting changes in cerebral blood flow (CBF), generally showing regional attenuation of faster frequencies and increases in slow activity; based on these observations, many authors have suggested cEEG for ischemia identification during surgical or neuroradiological procedures, during intracranial hypertension and for the diagnosis of delayed cerebral ischemia (DCI) after subarachnoid hemorrhage [22][23][24]. Although many studies have tried to show a specific ischemic pattern in various conditions, current recommendations suggest cEEG to detect ischemia only for the diagnosis of DCI after subarachnoid hemorrhage [5].…”
Section: Diagnosis Of Ischemiamentioning
confidence: 99%
“…Previous quantitative analysis studies typically focussed on specialized features to point out a disease or abnormality in the brain Chabot and Serfontein, 1996;Hughes and John, 1999;Bares et al, 2012;Prichep et al, 1994;Calzada-Reyes et al, 2011;Begić et al, 2011;Bjork et al, 2011;Jiang et al, 2011;Mishra et al, 2011). The di erence between these and our study, is that we a empt to quantify the same background properties reported by routine visual analysis, and in addition, compare the quantitative output to that of the human reviewer.…”
Section: Discussionmentioning
confidence: 88%